The Burden of Pediatric Encephalitis in the United States - Leena B. Mithal (Pediatric Neurology Briefs Publishers, 2016)
Investigators from the University of Maryland, University of Colorado, and Arkansas Children's Hospital studied the epidemiology, management and resource utilization of children admitted to hospitals in the United States with encephalitis.